Constrained Direct Optimisation of the Geometrical Parameters of a Twisted-Tape for Laminar Flow in a Circular Tube - Silva Junior, Luís G. [UNESP]; Silva, Felipe A. S. [UNESP]; Faria, Tiago G.; Kessler, Martin P.; Salviano, Leandro O. [UNESP] (Taylor & Francis, 2021)
Increasing heat transfer in heat exchangers remains an important research topic for industrial and residential applications. The usage of passive techniques remains a reference due to the lower costs, however, increasing the heat transfer in laminar flow with low-pressure loss remains a challenge. The objective of this paper is to perform a constrained optimisation of a twisted-tape inside a circular tube at low Reynolds number. Twisted tape pitch (P), length (L), translate (T), and twisted tape radius (R1 and R2) were submitted to optimisation. The flow is steady-state, laminar and incompressible. The NSGA-II is the method used for the optimisation procedure. The optimisation process found an optimal twisted-tape geometry with an asymmetric shape for both Reynolds numbers, corresponding to a global heat transfer increase of approximately 90% for Reynolds number 300 and 170% for Reynolds number 600, while for symmetric twisted-tape with ratio 4 (R4) is 57% and 52%, respectively.
Keywords: Enhancement heat transfer; numerical simulation; optimization; twisted-taped